Porte sculptée au Village du Kinh-Luoc - Auteur inconnu (Wikimedia Commons, 1945)
Notice image issue de Wikimedia Commons. Titre: Porte sculptée au Village du Kinh-Luoc. A postcard depicting the tomb of the Nguyn Dynasty Mandarin (and the Viceroy of Tonkin) Hoàng Cao Khi in the city of Hanoi, in the French protectorate of Tonkin.
Licence Public domain via Wikimedia Commons
Keywords: carte postale; image; patrimoine; architecture; histoire locale